Partisipasi Masyarakat dalam Penyelenggaraan PAUD di Daerah tertinggal Desa X - Sari Mulyati (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Early childhood education is very important, especially to prepare children to face the next level of education. The lack of human resources and the lack of government outreach to communities in disadvantaged areas related to early childhood education are feared to have an impact on the level of community participation in early childhood education, even though early childhood education is able to form quality children so that children grow and develop according to their stages. This study aims to find out how the community participates in organizing kindergarten education in X Village as well as supporting sources, namely village administrators, school principals, and parents of White Lotus Kindergarten students. Data collection techniques used interviews, data validity testing documentation used data triangulation. Data were analyzed through the stages of data collection, data reduction, and drawing conclusions. The results of this study are that the participation of parents in X Village in the implementation of Kindergarten education in X Village is quite low, because the funding for TK X still uses funds from the government and the village. and the implementation of ongoing education because of obligations that must be met, such as paying tuition fees and parents only participating by sending their children to TK X by wanting to participate if the school holds mutual cooperation activities. Abstrak. Pendidikan anak usia dini itu sangatlah penting terutama untuk mempersiapkan anak untuk menghadapi jenjang pendidikan selanjutnya. Minimnya sumber daya manusia dan kurangnya sosialisasi pemerintah terhadap masyarakat yang ada di daerah tertinggal terkait dengan Pendidikan Anak usia dini dikhawatirkan akan berdampak pada tingkat partisipasi masyarakat terhadap Pendidikan Anak usia dini, padahal Pendidikan Anak usia dini mampu membentuk anak berkualitas agar anak bertumbuh kembang sesuai dengan tahapannya. Penelitian ini bertujuan untuk mengetahui bagaimana partisipasi masyarakat dalam penyelenggaraan pendidikan taman kanak- kanak di Desa X seta sumber pendukung yaitu pengurus desa, kepala sekolah, dan orang tua murid TK X. Teknik pengumpulan data menggunakan wawancara, dokumentasi uji keabsahan data menggunakan triangulasi data. Hasil penelitian ini yaitu partisipasi orang tua di Desa X terhadap penyelenggaraan pendidikan Taman Kanak-kanak di Desa X cukup rendah, dikarenakan pendanaan di TK X masih menggunakan dana dari pemerintah dan desa serta penyelenggaraan pendidikan berjalan karena kewajiban-kewajiban yang harus dipenuhi seperti membayar SPP dan orang tua hanya berpartisipasi dengan menyekolahkan anak di TK X dengan mau ikut serta bila sekolah mengadakan kegiatan gotong royong.